Analisis Kesuksesan Website E-Care dengan Model Delone and Mclean Berdasarkan Persepsi Mahasiswa Universitas Dinamika - Delvia Sunarno Putri; Sulistiowati Sulistiowati; Nunuk Wahyuningtyas (Jurnal Sistem Informasi Universitas Dinamika, 2022)
Dinamika University (Undika) is one of the private universities in Surabaya. Undika has one of them is the service and counseling section. Counseling guidance services aim to help students develop themselves and overcome academic problems, social problems, and personal problems that affect the academic development of students. The problem is, as a website that is still relatively new, it is necessary to develop a website according to the Systems Development Life Cycle (SDLC) model, namely feedback at the Deployment stage. Therefore, in this final project, feedback was conducted in the form of an evaluation of the e-care.dinamika.ac.id website with the DeLone and McLean model. The DeLone and McLean model is used because in the DeLone and McLean model there are variables that contain system quality, information quality, and service quality. The DeLone and McLean model is also equipped with usage variables, user satisfaction variables, and net benefits variables.